EFFECTS OF SGLT-2 INHIBITORS ON 24H AMBULATORY BLOOD PRESSURE IN PATIENTS WITH TYPE 2 DIABETIC AND HYPERTENSION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (June 2022) - Wang, Qiongying; Tian, Li; Sun, Runmin; Qi, Miaomiao; Yu, Jing; Bai, Feng
Abstract : Objective: To analyze the effects of different types of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on 24-hour ambulatory blood pressure in patients with type 2 diabetes mellitus and hypertension. Design and method: In the meta-analysis, The PubMed, Web of science, and Cochrane Library were searched for relevant literature, and the references obtained from these sources were retrieved from inception till December 2020. The inclusion and exclusion criteria were formulated in accordance with the requirements of Cochrane systematic review. A total of 1354 articles were retrieved, 592 duplicate articles were excluded, 372 articles were excluded after reading the title and abstract, 87 articles were excluded from non-randomized control and irrelevant outcome indicators, and 7 studies with 2343 patients were finally included. Use RevMan5.3 software to compare the changes in 24-hour ambulatory blood pressure, day and night blood pressure of patients with type 2 diabetes and hypertension before and after treatment with different types and doses of SGLT2i. Results: A total of four types of SGLT-2i were evaluated in the application of patients with type 2 diabetes and hypertension. The result showed that compared with placebo, SGLT2i could reduce the 24-hour systolic blood pressure of patients with type 2 diabetes and hypertension by 4.36mmHg (95%CI -5.92--2.79, p < 0.001), among which the antihypertensive effects of empagliflozin, canagliflozin, dapagliflozin and ertugliflozin were -4.59mmHg, -3.74mmHg, -5.06mmHg, -3.64mmHg, respectively; similarly, the 24-hour dynamic diastolic blood pressure decreased by 2.20mmHg (95%CI -2.74, -1.65, p < 0.001), among which the antihypertensive effects of empagliflozin, canagliflozin, dapagliflozin and ertugliflozin were -2.38mmHg, -1.22mmHg, -2.00mmHg, - 2.69mmHg, respectively. At the same time, the systolic and diastolic blood pressure during the day and night decreased significantly. Conclusions: his meta-analysis shows that SGLT2i can have beneficial effects on the cardiovascular system by reducing 24-hour ambulatory blood pressure in patients with type 2 diabetes and hypertension, other than reducing blood sugar. Therefore, for patients with type 2 diabetes and hypertension, SGLT2i may be the best hypoglycemic choice.